دراسة التبادل الحراري الموضعي في حجرة احتراق محركات الاحتراق الداخلي - أيوب عيسى حسن -عارف علي (Latakia University Journal -Engineering Sciences Series, 2019)
إن الهدف من تطوير صناعة محركات الاحتراق الداخلي هو زيادة استطاعتها النوعية وتحسين اقتصاديتها في استهلاك الوقود، إضافةً إلى تخفيف التلوث الناتج عن عملها، إلا أن ذلك يترافق بزيادة الإجهادات الحرارية للعناصر الأساسية المكونة لحجرة الاحتراق، الأمر الذي يتطلب تغيير شروط التبادل الحراري ضمنها. يتضمن هذا البحث دراسة تحليلية تجريبية للتبادل الحراري ضمن حجرة الاحتراق وتوزع التيارات الحرارية فيها، بهدف تقييم حالة العناصر الداخلة في تشكيل هذه الحجرة والإجهادات الحرارية المؤثرة فيها، الأمر الذي يوفر بدوره المعلومات اللازمة لدراسة وتحسين دورة عمل المحرك وزيادة مردوده، واتخاذ التدابير التصميمية الملائمة للعناصر الأساسية للمحرك، التي تحدد موثوقية عمله وحسن أدائه وزيادة عمر خدمته. The aim of developing the engines of internal combustion is to increase its qualitative power by improving its economical fuel needs and reducing the pollution triggered by it. This will be accompanied with an increase in the thermal stresses of the basic parts of the combustion chamber. This requires changing its heat exchanging. The present paper includes an experimental, analytical study of heat exchanging in the combustion chamber, the heat flow distribution, evaluating the condition of the elements forming the chamber. These conditions in turn will provide the information required for studying and improving the internal combustion engine's action, cycle, efficiency, and taking the design measures appropriate to the basic components of the engine, hence determining its service and reliability.…